Eu3+ optical activation engineering in AlxGa1-xN nanowires for red solid-state nano-emitters. (March 2021) - Cardoso, J.; Jacopin, G.; Faye, D.Nd.; Siladie, A.M.; Daudin, B.; Alves, E.; Lorenz, K.; Monteiro, T.; Correia, M.R.; Ben Sedrine, N.
Abstract: In this work, Eu 3+ -implanted and annealed Al x Ga1- x N (0 ≤ x ≤ 1) nanowires (NWs) grown on GaN NW template on Si (111) substrates by plasma-assisted molecular beam epitaxy are studied by µ-Raman, cathodoluminescence (CL), nano-CL, and temperature-dependent steady-state photoluminescence (PL). The preferential location of the Eu 3+ -implanted ions is found to be at the Al x Ga1- x N top-section. The recovery of the as-grown crystalline properties is achieved after rapid thermal annealing (RTA). After RTA, the red emission of the Eu 3+ ions is attained for all the samples with below and above bandgap excitation. The 5 D0  →  7 F2 transition is the most intense one, experiencing a redshift with increasing AlN nominal content ( x ) from GaN to AlN NWs. Moreover, AlN nominal content and annealing temperature alter its spectral shape suggesting the presence of at least two distinct optically active Eu 3+ centers (Eu1 and Eu2). Thermal quenching of the Eu 3+ ions´ luminescence intensity, I, is determined for all the samples from 14 K to 300 K, being the emission of Eu 3+ -implanted AlN NWs after RTA at 1200 °C the most stable ( I 300 K / I 14 K ~80%). The GaN/AlN interface in this sample is also found to have a key role in the Eu 3+ optical activation. Graphical abstract: Image, graphical abstract